Relationship of Renal Echogenicity with Renal Pathology and Function - Jin Hee Lee; Myung Hyun Cho; Sung Ill Chung; So Dug Lim; Kyo Sun Kim (Korean Society of Pediatric Nephrology, 2017)
Purpose Renal ultrasonography has been widely used in children with renal disease. However, the relationship of renal echogenicity with renal pathology and function in children is not well known. Methods Ultrasound examination was performed in 75 patients undergoing renal biopsy for suspected renal disease in Konkuk University Medical Center from August 2005 to November 2015. We compared renal echogenicity to pathologic findings and renal function. Renal echogenicity was scored as 0 to 2 by comparing adjacent liver echogenicity. Three histologic characteristics were evaluated: glomerular changes, interstitial infiltration or fibrosis, and tubular atrophy. These were graded as 0 to 3, according to increasing severity. Laboratory results included urine albumin excretion and estimated glomerular filtration rate (eGFR). Results Among pathologic findings, renal echogenicity revealed a positive correlation with interstitial infiltration or fibrosis (r=0.259, p=0.025), and with tubular atrophy (r=0.268, p=0.02). Renal echogenicity and glomerular changes were not correlated . Renal echogenicity showed a positive correlation with microalbuminuria (r=0.283, p=0.014), but a negative correlation with eGFR (r=-0.352, p=0.002). Concluson Increased renal echogenicity suggested severe interstitial infiltration or fibrosis and tubular atrophy among the pathologic findings. Moreover, increased echogenicity is correlated with increased urine albumin excretion and decreased eGFR. Echogenicity on ultrasonography is useful for determining the status of renal pathology and function.